Stability of Encapsulated Lactobacillus reuteri during Harsh Conditions, Storage Period, and Simulated In Vitro Conditions - Abdolazim Soltani Lak; Mohammad Hossein Marhamatizadeh; Hossein Fattahi (Journal of Food Quality)
Viability of probiotics in the foods and human bodies is important, because a certain minimum count of bacteria is necessary to impose health promoting effects. In the present work, we encapsulated Lactobacillus reuteri within whey protein isolate (WPI), soy protein isolate (SPI), WPI + inulin (WPI4I), and SPI + inulin (SPI4I) through spray drying method and investigated the efficiency of the microcapsules on the protection of the cells under different conditions (heat, salt, bile salt, penicillin, pH, simulated gastrointestinal condition, and storage). The particle size of the samples was in the range of 195.2–358.1 nm. The sensitivity of unencapsulated bacteria to heat was considerably higher than that to the encapsulated bacteria, so that, at 80°C, no growth (of unencapsulated type) was observed. At 60°C and 40°C, the cell count of free bacteria decreased to 5.81 and 8.04 log CFU/mL, respectively. The bacteria encapsulated within SPI4I showed the highest viability at these temperatures. A comparison between the effects of different pH values showed pH 1.5 more lethal than 2.5 and 7. The effect of NaCl at 4% concentration on decreasing the bacterial count was more notable than 2%. However, the used wall materials in all conditions resulted in higher viability of the cells compared to the free cells. Among different types of wall materials, it was observed that WPI4I imposed the best protective effect. The higher viability of cells within WPI4I wall material was also observed during the storage time. The viability of encapsulated cells decreased from 10.35 to 10.40 log CFU/g in the first week and to 8.93–9.23 log CFU/g in the last week of storage.